Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $B, C, D, E$ are sets
Prove/Disprove: $(B \backslash C)\backslash (D\backslash E) = (B\backslash D)\backslash (C\backslash E)$

Any help would be much appreciated

share|cite|improve this question
This statement is false, try $C \subsetneq B = D = E$. – dtldarek Jan 31 '13 at 7:17
up vote 7 down vote accepted

These are fairly complicated-looking sets, so it may be easier to try to prove equality and see whether anything goes wrong.

Suppose that $x\in(B\setminus C)\setminus(D\setminus E)$. Then $x\in B\setminus C$, and $x\notin D\setminus E$. From the fact that $x\in B\setminus C$ we conclude that $x\in B$ and $x\notin C$. From the fact that $x\notin D\setminus E$ we conclude that either $x\notin D$, or $x\in D\cap E$.

Suppose first that $x\notin D$; then $x\in B\setminus D$. And since $x\notin C$, $x\notin C\setminus E$, and therefore $x\in(B\setminus D)\setminus(C\setminus E)$. If this were the only case, we could conclude that

$$(B\setminus C)\setminus(D\setminus E)\subseteq(B\setminus D)\setminus(C\setminus E)\;.$$

However, it isn’t: what if $x\in D\cap E$? In that case $x\notin B\setminus D$, so $x\notin(B\setminus D)\setminus(C\setminus E)$, and we cannot conclude that

$$(B\setminus C)\setminus(D\setminus E)\subseteq(B\setminus D)\setminus(C\setminus E)\;.$$

This looks like an insurmountable obstacle: to get a counterexample, we need only find $B,C,D$, and $E$ such that $(B\setminus C)\setminus(D\setminus E)$ has an element $x\in D\cap E$. That’s certainly possible if we take $D=E\ne\varnothing$. To be concrete, let $D=E=\{0\}$. We also need to be sure that $x\in B\setminus C$; a simple way to do that is to let $B=\{0\}$ as well and set $C=\varnothing$. Then

$$(B\setminus C)\setminus(D\setminus E)=\big(\{0\}\setminus\varnothing\big)\setminus\big(\{0\}\setminus\{0\}\big)=\{0\}\setminus\varnothing=\{0\}\;,$$


$$(B\setminus D)\setminus(C\setminus E)=\big(\{0\}\setminus\{0\}\big)\setminus\big(\varnothing\setminus\{0\}\big)=\varnothing\setminus\varnothing=\varnothing\;.$$

The statement is indeed false.

share|cite|improve this answer

Left side is

$$(B \cap \bar{C}) \cap \overline{(D\cap \bar{E})}=(B \cap \bar{C}) \cap (\bar{D} \cup E)=(B\cap \bar{C}\cap \bar{D})\cup (B\cap \bar{C}\cap E)$$

share|cite|improve this answer

If your system has a universe set $U$ then replace $B=E=U$ and use that $X\setminus U=\phi$ and that $X \setminus \phi=X.$ Then you have $$(U \setminus C) \setminus (D \setminus U)=(U \setminus D)\setminus(C\setminus U)$$ from which $$U \setminus C=U \setminus D.$$ In other words $C,D$ have the same complement, and you can conclude $C=D$.

So the statement is true (in the case $B=E=U$) when and only when $C=D$.

share|cite|improve this answer

By definition, $A \setminus B = A \cap B^c$. So $(B \setminus C) \setminus (D \setminus E) = B \cap C^c \cap(D \cap E^c)^c = (B \cap C^c)\cap(D^c \cup E) = (B \cap C^c \cap D^c)\cup(B \cap C^c \cap E)$

Looking at the second set, $(B \setminus D) \setminus (C \setminus E) = (B \cap D^c)\cap(C^c \cup E) = (C \cap B \cap D^c) \cup(B \cap D^C \cap E)$

It should be pretty clear from here that the sets aren't equal and how to come up with a counter-example.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.